Combustion and exergy analysis of multi-component diesel-DME-methanol blends in HCCI engine. (15th November 2019) - Taghavifar, Hadi; Nemati, Arash; Walther, Jens Honore
Abstract: A homogeneous compression ignition (HCCI) engine is taken for numerical investigation on the application of renewable fuels contained blends of methanol and DME with the base diesel fuel, which will be replaced with diesel in different percentages. First, the combustion and engine performance of the engine for two and three-component fuels will be discussed and secondly, the simultaneous effect of EGR in 20% by mass and engine speed in two blends of having maximum and minimum diesel proportion are compared and examined. The results indicate that the replacement of diesel with 20% of DME and 30% by methanol (D50M30DME20) at 1400 rpm generates a greater pressure and accumulated heat (AHRpeak = 330.569 J), whereas D80M20/2000 rpm/EGR20 gives a defective combustive performance with poor engine efficiency (IMEP = 7.21 bar). The interesting point is that the proposed optimum blend of D50 can achieve the best performance with 35% mechanical efficiency of 35%. The case of D60M10DME30 though dominates in terms of RPR = 3.177 bar/deg and ignition delay (ID = 4.54 CA) that gives the highest exergy performance coefficient (EPC = 2.063) due to its high work and lowest irreversibility. Highlights: A three component fuel combustion of diesel-DME-methanol investigation in HCCI engine. The feasibility of DME and methanol replacement with diesel is evaluated in advanced exergetic framework. The effect of 20% EGR on rate of pressure rise and ignition delay of blended fuel is considered. D50 fuel exceeds in mechanical efficiency, D60 in exergy performance coefficient and lower irreversibility. D80 shows minimum work exergy and maximum irreversibility.